ORGANIZATION OF SPORTS WORK IN HIGHER EDUCATIONAL INSTITUTIONS - Gapparov Khafiz Zakhidovich; Hikmatilla Rakhmanberdievich Akhmedov (Scholar Express Journal, 2022)
The article reveals the main provisions of the organization and holding of sports competitions in higher educational institutions, as well as the concepts of competitions and the main issues.
Keywords: Competition; Student's Physical Training; Championship; provisions